(untitled) (Development Service Industry Management, 2024)
In today’s conditions of globalization and intensification of foreign economic activity of enterprises, effective management of business projects related to transportation is a key factor in their successful implementation. An important aspect is the integration of environmental, social and economic factors into logistics processes, which corresponds to the global goals of sustainable development. The article examines the main stages of business project management in the field of transport logistics of enterprises focused on foreign economic activity, as well as factors affecting their successful implementation. In particular, the role of transport infrastructure, the choice of optimal types of transport for international transportation, as well as the use of innovative technologies in transport logistics are analyzed. Four key stages of transport business project management are revealed: planning, organization, monitoring and control, completion and evaluation of results. The article also considers the introduction of innovations in the transport logistics of foreign economic activity, in particular the digitization of processes through the use of transport management systems and supply chain management systems. The use of modern technologies makes it possible to optimize routes, reduce costs, improve transportation monitoring and increase the overall efficiency of transport operations. Special attention is paid to environmental aspects in transport logistics. The article highlights the importance of using environmentally friendly modes of transport and implementing the principles of green logistics, which contribute to reducing the negative impact on the environment. Enterprises that integrate environmental aspects into their business processes receive advantages in the international market, in particular through increased reputation and compliance with global goals of sustainable development. The integration of innovative solutions and consideration of environmental factors allow to adapt the activities of enterprises to new market requirements and contribute to the long-term success of business in conditions of sustainable development.